Strategi Fundraising Gerai Zakat, Infak, Shadaqah dan Wakaf Melalui Mall/Pusat Perbelanjaan di Jabodetabek - Nurul Hidayati; Tony Surkancana (Jurnal Manajemen Dakwah, 2019)
The objective of this studywas to obtain a general overview of optimizingvfundraising strategies by zakat, infaq, shadaqah, and waqf and how to take care of licensing the opening of zakat outlets through malls / shopping centers in Greater Jakarta. Fred R. David manages strategy management with 3 steps, strategy formulation, strategy implementation, and strategy evaluation. While the purpose of fundraising according to Furqon and Ibrahim, there are five of them; they are collectingzakat funds, adding Muzakki, building the image of an institution, collecting sympathizers / relationships, satisfying donors and muzakki. This research focuses on fundraising strategies for Zakat, Infaq, Sadaqah and Waqf outlets through Shopping Centers in Greater Jakarta, using a qualitative research approach. Zakat outlets were examined 6 malls, 2 shopping centers, and 1 zakat headquarters. The results of his researchare that there are differences between official institutions as amilzakat and unofficial ones even though they have formed an Islamic social foundation. They arein institutions that are in the form of foundations but not yet officially as amilzakat institutions, 1. There is no zakat education 2. no audits 3. No reports 4. Less than optimal in fundraising strategies. 5. The program is not used as a fundraising strategy. 6. less ethical. Institutions in the form of foundations and unofficially emphasize the distribution of funds while in the case of raising zakat funds are less accountable. Meanwhile, the amilzakat institution emphasizes the raising of zakat funds in accordance with the name of the institution, namely the amilzakat institution.